Rotary motion transmission and stabilization devices - Bogdevičius, Marijonas; Jurevičius, Jurgis; Spruogis, Bronislovas (Transport, 2004)
To connect rotors, to transmit and stabilize rotation motion a new class of rotary motion transmission and stabilization devices (RMTSD) was developed. They include the rings which deform axialy, radially and at an angle the radial segments, etc. with joined concentrated inertial, dissipative and elastic elements. RMTSD design schemes are copyrighted and covered by the patents of the USA, England and Germany. The classification of RMTSD development is performed according to the following characteristic features: dynamic characteristics, kind of elastically creeping elements, peculiarities of design elements, fastening, materials, etc. The classification presented gives the possibility to develop lots of constructions of new RMTSD of this type. First Published Online: 27 Oct 2010